Hematological parameters’ reference intervals in apparently healthy individuals in Saudi Arabia: a systematic review and meta-analysis - Shaheen, Naila; Thomas, Seena; Almoghairi, Areej; Alaskar, Ahmed (Frontiers in Medicine, 2025)
BackgroundThe study aimed to perform a systematic review/meta-analysis of observational studies conducted in Saudi Arabia to identify the patterns of reported hematological parameters’ reference intervals (RIs).MethodsThe literature search was performed using PubMed and Google Scholar. Observational studies that reported hematological parameters measured under normal physiological conditions in apparently healthy individuals were included. Studies conducted on non-healthy individuals and/or on pregnant women; those related to basic science, methodology, physiology, and non-physiological state; and those conducted on patients having co-morbidities were excluded. Studies on the pediatric population were also excluded from the meta-analysis. The methodological quality was assessed using standard critical appraisal instruments from the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. R software was used to run the random-effects models. The results were reported as weighted mean differences and 95% confidence intervals. The complete blood count (CBC) parameter means were compared by sex using an independent samples t-test.ResultsIn total, 12 studies were included in the systematic review from all regions—Central (n = 5), Western (n = 5), Southern (n = 1), and Northern (n = 1). A total of eight (66%) studies focused on adults, and four (33.3%) studies reported a sample of adolescents/children. In addition, seven studies were not included in the meta-analysis for the following reasons: three studies reported only white blood cell (WBC) parameters, two studies had only abstracts available, and two studies involved newborns. High heterogeneity was demonstrated for all hematological parameters: red blood cell (RBC), hemoglobin (Hb), or mean corpuscular hemoglobin concentration (MCHC) (I2 = 100%); mean corpuscular hemoglobin (MCH) or hematocrit (HCT) (I2 = 99%); platelet (PLT) or mean corpuscular volume (MCV) (I2 = 98%); and WBC (I2 = 90%). The RBC (p = 0.009) and Hb (p = 0.0006) values were higher in the male participants. The PLT (p = <0.0001) values were higher in female participants. The remaining hematological parameters’ RIs were not statistically significant.ConclusionThe findings indicated some differences in the hematological parameters’ RIs reported across Saudi Arabia. We recommend establishing hematological parameters’ RIs based on the Saudi Arabian population to determine when to refer a patient with abnormal counts and to identify when to request further diagnostic work-up.